2018
DOI: 10.46370/sajfte.2018.v04i02.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sub-lethal concentrations of crude oil on tomato yield and quality

Abstract: Heavy crude oil spills have been recorded to have detrimental effects on the soil properties of agricultural lands and the eventual agricultural produce. However, the influence of sub-lethal concentrations of crude oil on crop quality is not clearly understood. Hence, the present study assessed the response of Micro-Tom tomato fruits to low concentrations of crude oil. Although the range of crude oil concentrations used in this research had no significant effect on most of the nutritional and phytochemical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Source: Odukoya [5]. Odukoya et al [5,22] also recorded that crude oil contamination at concentration as low as 5000 mg/kg TPH affected the growth, yield, fruit production, and ripening of Micro-Tom tomato fruits ( Figure 5). Odukoya et al [5,22] also recorded that crude oil contamination at concentration as low as 5000 mg/kg TPH affected the growth, yield, fruit production, and ripening of Micro-Tom tomato fruits ( Figure 5).…”
Section: Effects Of Ph On the Growing Environment And Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Odukoya [5]. Odukoya et al [5,22] also recorded that crude oil contamination at concentration as low as 5000 mg/kg TPH affected the growth, yield, fruit production, and ripening of Micro-Tom tomato fruits ( Figure 5). Odukoya et al [5,22] also recorded that crude oil contamination at concentration as low as 5000 mg/kg TPH affected the growth, yield, fruit production, and ripening of Micro-Tom tomato fruits ( Figure 5).…”
Section: Effects Of Ph On the Growing Environment And Plantsmentioning
confidence: 99%
“…Retardation of plant growth may also occur as the plants make efforts to conserve and reallocate resources that can become limited under extreme stress conditions [48]. Odukoya et al [5,22] also recorded that crude oil contamination at concentration as low as 5000 mg/kg TPH affected the growth, yield, fruit production, and ripening of Micro-Tom tomato fruits ( Figure 5). Considering the effect of time of spillage on plant response, Baker [38] reported that application of an emulsion of light oil on young plants in the light when the stomata are opened will lead to death of the plant while the same application at night when the stomata are closed would not harm them.…”
Section: Abiotic Environmental Stresses and Crop Qualitymentioning
confidence: 99%